AB 37. Synchronous large cell neuroendocrine carcinoma of the lung and hepatocellular carcinoma of the liver: a case report - Cheva, Aggeliki (Pioneer Bioscience Publishing Company, 2012)
BACKGROUND: Large cell neuroendocrine carcinoma is part of the neuroendocrine spectrum of pulmonary tumors and represents 3% of all lung cancers. The incidence of synchronous or metachronous primary malignancies is increased in patients with neuroendocrine carcinomas. The etiology is unclear, but it may be related to the fact that neuroendocrine carcinomas produce and release growth factors that may be involved in the tumor genesis of other neoplasia. We report a case of large cell neuroendocrine carcinoma synchronous with a hepatocellular carcinoma in the liver. PATIENTS AND METHODS: A 66-year-old man was presented to our hospital with cough, dyspnea and haemoptysis. A nodule was detected in the right lung and another one in the liver by computed axial tomography (CT scan). Lung biopsy and CT-guided fine needle biopsy of the liver were followed. RESULTS: Histologically, the lung tumor was composed of medium to large-sized pleomorphic cells, with scant cytoplasm, inconspicuous nucleoli, high mitotic activity, crushing artifact and zones of necrosis. Immunohistochemical stains were positive for CD56, TTF-1, AE1/AE3, chromogranin (pale stain), whereas they were negative for CK7 and synaptophysin. Ki-67 was expressed in 50% of neoplastic cells. Diagnosis: Primary large cell neuroendocrine carcinoma of lung. The liver biopsy revealed hepatic cells, focally atypical with presence of mitosis. Immunohistochemically, these cells were positive for hepatocyte and CEA poly (focally) and negative for CEA mono, CD56, TTF-1 and synaptophysin. Diagnosis: Well-differentiated hepatocellular carcinoma. CONCLUSIONS: Neuroendocrine carcinoma’s association with other malignancies is an increasingly appreciated phenomenon. So, every patient diagnosed with neuroendocrine carcinoma should undergo thorough investigation for concomitant other neoplasm.